Elastoplastic analysis of cracked Aluminum plates with a hybrid repair technique using the bonded composite patch and drilling hole in opening mode I - Wahiba Nessrine Bouzitouna; Wahid Oudad; Mohamed Belhamiani; Djamel Eddine Belhadri; Leila Zouambi (Fracture and Structural Integrity)
The objective of this study is to analyze the performance of composite bonding repair, hole drilling and the combination of the two techniques (hybrid repairs) by tensile tests and to show the interest of a hybrid repair versus to other processes. These repair techniques can apply in different branches of engineering: mechanical, aerospace, civil, naval, etc. The finite element method with the ABAQUS code was used to model the mechanical behavior of the different repair techniques. The Notch Stress Intensity Factor (NSIF) is adopted to model the behavior of the cracked notch based on the volumetric method. The size of the plastic zone, the intensity of the normal σyy stress, the peel stress and CTOD are combined to model the proposed technics repairs. Although the bonded composite is very strong, the application of a drilling hole results in additional energy absorption and reduces the level of the maximum normal stress by about 50% compared to a simple patch only. The use of a hybrid repair has a high resistance compared to other proposed methods, improves the mechanical strength and increases the life of the cracked structure compared to a single composite joint and a repair by drilling hole only.